THEORETICAL FOUNDATIONS OF ACCOUNTING OF INCOME AND EXPENSES OF INSURANCE ORGANIZATIONS. - Kuvatova Dinara (Scholar Express Journals, 2024)
This article explores the theoretical foundations of accounting for income and expenses within insurance organizations. It provides an in-depth analysis of the principles and methodologies that govern the financial recording and reporting of insurance operations. The discussion encompasses the classification and recognition of various income sources, including premiums, investment returns, and reinsurance recoveries, as well as the accounting treatment of expenses such as claims payments, underwriting expenses, and administrative costs. By examining accounting standards, regulatory frameworks, and industry practices, this article aims to elucidate the complexities of insurance accounting and highlight best practices for accurate financial reporting. The findings underscore the importance of adhering to established accounting principles to ensure transparency, regulatory compliance, and informed decision-making within insurance companies
Keywords: Insurance accounting; regulatory frameworks; expense management